Somatotype of male and female judokas according to weight categories - Roklicer, R.; Atanasov, D.; Sadri, F.; Jahic, D.; Bojanic, D.; Ljubojevic, M.; Trivic, T.; Drid, P. (Biomedical Human Kinetics, 2020)
Study aim: The body structure can play a determining role in the achievement of top judo performance, and it seems to influence the type of techniques applied. The aim of this study is to determine the somatotypes in male and female national level judokas across weight categories in order to observe possible differences among athletes.